Sheriff of Hangtown [large type] : a western duo - Paine, Lauran (Wheeler Publishing large print western, 2009)
This duo combines two book-length Western stories by the incomparable Lauran Paine, marked by his characteristic authenticity and strong characters. In "Outlaw's Hide-Out," drifter Hap Thompson has lived in a secluded valley since robbing a bank made him a wanted man. But his tranquil life is interrupted when he discovers a strange horse and tracks it back to an injured young woman. Wesley Potter is the "Sheriff of Hangtown," and friend to Dick Ruffin, an old-timer who has long raised horses on his small ranch. When Ruffin is shot at close range without apparent motive, Potter has no clues or suspects.